Small Business Taxes For Dummies - Tyson, Eric (For Dummies, 2022)
Get your taxes right the first time and save USD If you run a small business, you've likely got more work than you already feel able to handle. The last thing you need is to be running around trying to figure out your taxes at the last minute. So, if you need a hands-on guide to small business taxes that doesn't mess around, look no further than Small Business Taxes For Dummies. In this book, nationally recognized personal finance expert Eric Tyson clearly and concisely delivers the best methods to save on your taxes and make the process as easy as possible. You'll get the latest info about all the newest tax deductions and credits (including COVID-19-related breaks), as well as location-specific incentives and other little-known tips. You'll also find: Expanded discussions of new retirement account options for small business owners The latest advice on how to deal with online and software tax prep and filing options to make life easier at tax time Explorations of likely new changes coming A can't-miss resource for small business owners, managers, and employees, Small Business Taxes For Dummies is the book to help you make sure you don't pay more than you need to pay at tax time!.